Use of Probiotics as Adjuncts in Non-Surgical Periodontal Therapy: A Literature Review (2024)
Introduction: Periodontitis is a chronic inflammatory disease associated with dysbiotic plaque biofilms, characterized by clinical attachment loss (CAL) and alveolar bone loss, which negatively impacts quality of life. There are several treatment approaches, including surgical methods and the use of antibiotics, but limitations and bacterial resistance have led to the search for more effective alternatives. Probiotics may inhibit the recolonization of periodontopathogens through direct and indirect mechanisms. However, evidence regarding their efficacy in the treatment of periodontitis is still inconclusive due to the diversity of methodologies in the studies. Objective: Review the existing literature to evaluate the benefits of probiotics as adjuncts in non-surgical periodontal therapy. Materials and Methods: A search was conducted in electronic databases (PubMed) up to September 2024 for randomized controlled trials (RCTs) comparing scaling and root planing (SRP) combined with probiotics versus SRP alone or with placebo. The outcome variables evaluated included clinical periodontal parameters, immunological and microbiological monitoring. Results: Twelve RCTs were included that evaluated clinical periodontal, microbiological, and immunological parameters. Five demonstrated effectiveness in improving clinical periodontal parameters, four showed a reduction in periodontal pathogens, and three found improvements in the immune response of patients using probiotics as adjuncts to scaling and root planing (SRP). Conclusions: Studies indicate that probiotic supplementation could improve clinical, microbiological, and immunological parameters in patients with periodontal disease. However, the effectiveness of these probiotics varies depending on the formulation, method of administration, duration of treatment, and type of periodontal disease. Longterm randomized controlled trials (RCTs) are needed to confirm the efficacy of probiotics as adjuncts in periodontal treatment and to assess their impact on health over time